Two Novel Phenolic Compounds from the Rhizomes of Cyperus rotundus L. - Zhongliu Zhou; Wenqing Yin (Molecules, 2012)
Two novel compounds, 1α-methoxy-3β-hydroxy-4α-(3′,4′-dihydroxyphenyl)-1, 2,3,4-tetrahydronaphthalin (1) and 1α,3β-dihydroxy-4α-(3′,4′-dihydroxyphenyl)-1,2,3,4-tetrahydronaphthalin (2), were isolated along with six known compounds 3–8 from the rhizomes of Cyperus rotundus. This paper reports the isolation and full spectroscopic characterization of these new compounds by NMR, UV, IR and MS data.